Expanding the phenotype of de novo SLC25A4-linked mitochondrial disease to include mild myopathy. (August 2018) - King, Martin S.; Thompson, Kyle; Hopton, Sila; He, Langping; Kunji, Edmund R.S.; Taylor, Robert W.; Ortiz-Gonzalez, Xilma R.
Abstract : Objective: To determine the disease relevance of a novel de novo dominant variant in the SLC25A4 gene, encoding the muscle mitochondrial adenosine diphosphate (ADP)/adenosine triphosphate (ATP) carrier, identified in a child presenting with a previously unreported phenotype of mild childhood-onset myopathy. Methods: Immunohistochemical and western blot analysis of the patient's muscle tissue were used to assay for the evidence of mitochondrial myopathy and for complex I–V protein levels. To determine the effect of a putative pathogenic p.Lys33Gln variant on ADP/ATP transport, the mutant protein was expressed in Lactococcus lactis and its transport activity was assessed with fused membrane vesicles. Results: Our data demonstrate that the heterozygous c.97A>T (p.Lys33Gln) SLC25A4 variant is associated with classic muscle biopsy findings of mitochondrial myopathy (cytochrome c oxidase [COX]-deficient and ragged blue fibers), significantly impaired ADP/ATP transport in Lactococcus lactis and decreased complex I, III, and IV protein levels in patient's skeletal muscle. Nonetheless, the expression levels of the total ADP/ATP carrier (AAC) content in the muscle biopsy was largely unaffected. Conclusions: This report further expands the clinical phenotype of de novo dominant SLC25A4 mutations to a childhood-onset, mild skeletal myopathy, without evidence of previously reported clinical features associated with SLC25A4 -associated disease, such as cardiomyopathy, encephalopathy or ophthalmoplegia. The most likely reason for the milder disease phenotype is that the overall AAC expression levels were not affected, meaning that expression of the wild-type allele and other isoforms may in part have compensated for the impaired mutant variant.